Design and development of micro hydro power at kampung semulong ulu (environmental impacts and social-economic impacts) - Wong, Yit Sen (Universiti Malaysia Sarawak, UNIMAS, 2010)
The study of environmental impacts and social-economic impacts is an important element need to be considered before construct any micro hydro power at underserved community. This study was aimed to identify the problems occur at reservoir, penstock, environmental impacts and social-economic impacts for micro hydropower. Problems of the reservoir and penstock will be determined and improved. Knowledge of both impacts help in understanding the underserved community and it works as a base for further study and inventions. The Kampung Semulong Ulu which is an underserved community has been chosen in this study. The interview was held in this village and it took 3 days and 2 nights. The interview was done on 30 participates from the Kampung Semulong Ulu and it was about the environmental impacts and social-economic impacts after the implementation for micro hydropower. Conclusion is based on the analysis and discussion after the interview.